2020
DOI: 10.3390/ijerph18010265
|View full text |Cite
|
Sign up to set email alerts
|

Creative Music Therapy with Premature Infants and Their Parents: A Mixed-Method Pilot Study on Parents’ Anxiety, Stress and Depressive Symptoms and Parent–Infant Attachment

Abstract: Premature birth is stressful for infants and parents and can adversely affect the parent–infant dyad. This mixed-methods pilot study evaluates whether creative music therapy (CMT) can alleviate anxiety, stress, and depressive symptoms in parents and support the bonding process with their infant. Sixteen parent couples were included. Ten couples were randomly allocated to the music therapy group (MTG) and six to the control group (CG). All couples completed psychological questionnaires measuring anxiety and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 51 publications
4
34
1
11
Order By: Relevance
“…In our study, an important reduction in maternal state anxiety was seen after LMPT, compared with the waitlist period. Our results correspond with those of Kehl et al, who found a reduction in anxiety levels in mothers whose preterm infants received creative music therapy [ 23 ]. Creative music therapy in their study consisted of humming or singing by a music therapist, preferably in the presence of the parents who had skin-to-skin contact with their child, and was accompanied by vibroacoustic stimulation by an instrument manufactured for therapeutic purposes.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, an important reduction in maternal state anxiety was seen after LMPT, compared with the waitlist period. Our results correspond with those of Kehl et al, who found a reduction in anxiety levels in mothers whose preterm infants received creative music therapy [ 23 ]. Creative music therapy in their study consisted of humming or singing by a music therapist, preferably in the presence of the parents who had skin-to-skin contact with their child, and was accompanied by vibroacoustic stimulation by an instrument manufactured for therapeutic purposes.…”
Section: Discussionsupporting
confidence: 92%
“…We therefore advocate starting music therapy early, to accelerate maternal anxiety reduction during NICU stay. Indeed, Kehl and colleagues reported a significant reduction in state anxiety levels after only six music therapy sessions, which started after the first week of the infants’ life [ 23 ]. Interestingly, several studies argue that there may even be a role for music therapy during pregnancy, evidenced by the reduction of maternal anxiety following such interventions [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A relative strength of this study is that CMT is noninvasive, low-cost, and family-integrating approach and we used standardized routine long-term clinically relevant measures of neurodevelopment to evaluate the intervention. Future trials could investigate parental psychological adjustment and bonding as preliminary evidence suggests that CMT contributes to parental empowerment and activates "communicative musicality" (64) thereby benefiting parent-infant-attachment (21,65,66). Interventions that support parent-infant attachment in early life may enhance infant socioemotional development, mental health and future relationships (67,68).…”
Section: Discussionmentioning
confidence: 99%